Dendaan Ke Atas Kanak-Kanak - Daud Hamzah, Mohamed (Penerbit Universiti Sains Malaysia, 1987)
Parents may use power-assertion and love-withdrawal strategies to control children's deviant behaviour. This paper focusses only on the use of power-assertion. Furthermore It Is limited to the physical punishment techniques within this strategy. This paper reveals that there is a range of physical punishment techniques starting from very mild reprimand to shouting, pinching, flieklng, smacking, flogging and outright physical torturing. It then reports a three-part survey on the extent Malaysian parents employ physical punishment techniques of shouting, pinching, flicking, smacking and flogging.